2021
DOI: 10.3389/fpls.2021.678197
|View full text |Cite
|
Sign up to set email alerts
|

Effect of LED Spectrum on the Quality and Nitrogen Metabolism of Lettuce Under Recycled Hydroponics

Abstract: Light quality optimization is an efficient method for improving the growth and quality of lettuce in plant factories. In this study, lettuce seedlings were illuminated under different light-emitting diode (LED) lights, namely, red-blue (RB), red-blue-green (RBG), red-blue-purple (RBP), and red-blue-far-red (RBF) LED lights, to investigate the effect of light quality on growth, quality, and nitrogen metabolism. The combination of 75% red and 25% blue light was set as the basic light source, and 20% of green, pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 46 publications
1
26
0
Order By: Relevance
“…A few studies on the composition of lettuce metabolites in hydroponic systems have been reported [ 37 , 38 , 39 ]. It has not been fully explored how different NH 4 + /NO 3 − ratios affect the sugar compounds, amino acid contents and polyphenolic compounds in lettuce and how these metabolic changes influence nutritional values in lettuce.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies on the composition of lettuce metabolites in hydroponic systems have been reported [ 37 , 38 , 39 ]. It has not been fully explored how different NH 4 + /NO 3 − ratios affect the sugar compounds, amino acid contents and polyphenolic compounds in lettuce and how these metabolic changes influence nutritional values in lettuce.…”
Section: Introductionmentioning
confidence: 99%
“…The gas exchange, chlorophyll fluorescence, and P700 redox state were measured in vivo by using the LI-6400XT Photosynthesis System (Li-Cor Incorporation, United States) and the Dual PAM-100F (Heinz Walz, Effeltrich, Germany) as described in previous reports ( Grieco et al, 2012 ; Pietrzykowska et al, 2014 ). The light-adapted curves were recorded after 2 min of exposure to various PPFDs ( Lu et al, 2019 ; Li et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Phy A is the predominant photoreceptor of far-red (FR) light and phy B is the primary photoreceptor of red (R) light ( Chen and Chory, 2011 ). In addition, the transcription factor ELONGATED HYPOCOTYL5 (HY5) can be activated by photoreceptors to promote downstream photomorphogenesis ( Li et al, 2021 ). Many studies have shown that the above molecules play key roles in cold tolerance ( Chen and Chory, 2011 ; Li et al, 2021 ; Wang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations